Cardano shared send transactions untangling in numbers - Mostafa Chegenizadeh; Nickolay Larionov; Sina Rafati Niya; Yury Yanovich; Claudio J. Tessone (Blockchain: Research and Applications, 2025)
In this paper, we analyze shared send mixers (SSMs) within Cardano's extended unspent transaction output (EUTXO) model, presenting significant contributions to the understanding of UTXO-based blockchains. Firstly, we define the EUTXO SSM untangling problem and propose an algorithm to address it, along with providing an open-source implementation of the solution. Utilizing real transaction examples, we formulate and solve this problem in a systematic manner, shedding light on the intricacies of coin circulation within the Cardano blockchain. Through our analysis, we reveal some insights into the usage of SSMs, including statistics on their frequency and effectiveness in untangling transactions. With this method, our findings show that 11% of transactions seem to involve SSMs, 83% of which enable unique untangling. Moreover, we discuss the potential application of our algorithm in enhancing the address clustering results of transaction-level heuristics. Overall, our work contributes to a deeper understanding of transactional dynamics within UTXO cryptocurrencies, particularly within the context of Cardano's EUTXO model.